Continuous hydrogenation of cinnamaldehyde: gas-liquid-liquid-solid helical coil reactor - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2023)
The advantages and challenges of using the gas-liquid-liquid-solid(GLLS) hydrogenation system are discussed in this work using the caseof selective hydrogenation of cinnamaldehyde to cinnamyl alcohol (animportant ingredient in the perfume and flavoring industry). The fourphases in this system include gas (hydrogen)-liquid (organic, reactant+ solvent)-liquid (aqueous KOH)-solid (5% Pt/C catalyst). The additionof second liquid phase, i.e., aqueous KOH significantly increasesselectivity toward cinnamyl alcohol compared to the conventional three-phasehydrogenation. The four-phase GLLS reactions were carried out andoptimized in a continuous helical coil reactor. The role of key aspectssuch as gas solubility, kinetics, flow hydrodynamics, axial dispersion,and mass transfer on the performance of a continuous GLLS reactoris presented and discussed in this work. The presented results anddiscussion will be useful for addressing conflicting demands likelong residence time, low axial dispersion, and high mass transfer.The experimental studies and results of the developed mathematicalmodel indicate that the continuous GLLS helical coil reactor outperformsthe batch operation. The production rates (kg day(-1)) of cinnamyl alcohol achieved in continuous operation were at leastdouble in comparison to batch operation, with 32% less consumptionof precious catalyst (per kg of product). The presented results will open up new opportunities for enhancing selectivity and overall performanceof hydrogenations via introducing a second immiscible liquid phaseand designing continuous tubular reactors for the same.